Programmed cell death ligand‐1 protein expression and CD274/PD‐L1 gene amplification in colorectal cancer: Implications for prognosis. Issue 9 (26th July 2018) - Lee, Kyu Sang; Kim, Bo Hyung; Oh, Heung‐Kwon; Kim, Duck‐Woo; Kang, Sung‐Bum; Kim, Hyunchul; Shin, Eun
Abstract : Programmed cell death ligand‐1 (PD‐L1) detection assays have not been standardized for patients with colorectal cancer, and the prognostic value of PD‐L1 expression is unclear. We compared the PD‐L1 expression patterns in colorectal cancer samples using various immunohistochemical assays using 3 primary PD‐L1 antibodies (assay 1, MIH1; assay 2, E1L3; and assay 3, 22C3) and investigated the prognostic implication of PD‐L1 expression using each. Additionally, PD‐L1 gene amplification was evaluated using FISH. The percentage scorings and positivity rates of the 3 assays differed; the degrees of correlation and concordance between assays 2 and 3 were relatively high, whereas assay 1 was an outlier. Multivariate analyses indicated that PD‐L1 positivity in tumor cells and its negativity in tumor‐infiltrating lymphocytes were independent predictors of poorer overall and disease‐free survival in patients with colorectal cancer. PD‐L1 gene amplification was found in 2 patients ( PD‐L1/CEP ratio, 5.60 and 5.84, respectively); both had strong PD‐L1 expression according to immunohistochemistry. Overall, our study showed that PD‐L1 expression status in tumor and immune cells is an independent prognostic factor in patients with colorectal cancer. Standardizations of both PD‐L1 detection using immunohistochemistry and the cut‐off for positivity are necessary. Finally, PD‐L1 gene amplification was found in a small fraction of samples, suggesting the possibility of an ancillary test for PD‐L1 evaluation. Abstract : We undertook this study to evaluate programmed cell death ligand‐1 (PD‐L1) expression in colorectal cancer with immunohistochemistry using 3 different antibodies as well as multiple cut‐off points for denoting PD‐L1 positivity. We also evaluated the CD274 / PD‐L1 gene copy number in colorectal cancers using FISH.